2019
DOI: 10.1021/acs.inorgchem.9b02230
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Supported Nanostructured NiFeCoPr Hydroxide as a High-Performance Supercapacitor Electrode and Electrocatalyst toward the Oxygen Evolution Reaction

Abstract: Facile and high-performance electrode materials are crucial for the conversion and storage of clean energy. A gold-supported nanostructured NiFeCoPr hydroxide is synthesized by directly electrodepositing praseodymium-doped nickel–cobalt–iron hydroxide onto a gold-deposited nickel foam (NF) substrate. The resultant monolithic NiFeCoPrO-Au/NF electrode exhibits a high specific capacitance (1792 F g–1 at a current density of 10 A g–1), excellent rate capability (1445 F g–1 at a current density of 70 A g–1), and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 89 publications
0
41
0
Order By: Relevance
“…11 Besides, water-insalt electrolytes and some electrolyte additives have also been adopted to inhibit the side reactions and dendrites. 12,13 Introducing a protective layer on the zinc anode has also drawn growing attention because of its good operability. For example, Xia et al recently reported the construction of a ZrO 2 -coated zinc anode.…”
Section: Introductionmentioning
confidence: 99%
“…11 Besides, water-insalt electrolytes and some electrolyte additives have also been adopted to inhibit the side reactions and dendrites. 12,13 Introducing a protective layer on the zinc anode has also drawn growing attention because of its good operability. For example, Xia et al recently reported the construction of a ZrO 2 -coated zinc anode.…”
Section: Introductionmentioning
confidence: 99%
“…Open demonstrated the coexistence of Co 3+ (780.8 eV) and Co 2+ (783.7 eV) and the main ingredient was Co 3+ . 44 As displayed in Figure 3e, the deconvolution of O 1s spectrum gave a hint for the presence of the adsorbed water (532.1 eV), hydroxide or oxyhydroxide group (-OOH or -OH, 531.2 eV), and lattice oxygen bonds (O-M, 529.6 eV), 25,45 where -OH/-OOH groups were found to be the major oxygen component. According to the XPS analysis (Table S1 Field-emission scanning electron microscopy (FE-SEM) analysis was implemented to identify the structural feature and morphology of the title electrode HS-Te-NiCo-LDH/NiO/NF (Figure 4).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 93%
“…For the efficient doping of metal or non-metal elements into heteromultimetallic hydroxides, electrochemical deposition has proven to be a rapid and practical method. 25 Besides, electrode materials with macro/micro/mesoporous hierarchical structures are highly favorable for the superior electrochemical performance in view of the more active sites, shorter paths for charge transfer, and improved charge-discharge efficiency. 26,27 On the one hand, the three-dimensional (3D) nickel foam (NF) can be used as the substrate to provide macropores, as well as the high specific surface area and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A monolithic electrocatalyst was designed for OER activity based on the electrodeposition of a rare-earth praseodymium-doped nickel−cobalt−iron hydroxide (NiFeCoPrO) onto a gold-deposited nickel foam (NF) substrate [ 63 ]. NiFeCoPrOAu/NF appeared in a size range between 2 and 80 nm, with a peak volume of ~3.5 nm.…”
Section: Functionalized Electrode Materials For Oermentioning
confidence: 99%